Dielectric properties of the small granular agricultural products in the microwave frequency band - RUNENG, ZHONG; QINHONG, ZHENG (The Indian Journal of Agricultural Sciences, 2020)
Microwave drying and non-destructive sensing of agricultural products based on dielectric properties is an important field of modern agricultural research. The present study was carried out to improve the traditional coaxial transmission line technology and get some basic dielectric properties of agricultural products from Yunnan province of China during year 2018-19. The effective dielectric properties of vegetable seeds, coarse cereals, and grass seeds form china are measured by a non-calibrated coaxial transmission reflection method at 2~6 GHz in this work. The dielectric properties of the small granular agricultural products are obtained by relevant theoretical formulas, and variations in the dielectric properties of granular agricultural products as a function of the microwave frequency and moisture content were analysed. The results show that the dielectric properties of small granular agricultural products at room temperature are related to the microwave frequency and moisture content with a certain degree of regularity. At 2.45 GHz and for a moisture content between 2%~25%, the dielectric constants and dielectric loss factors for different kinds of small granular agricultural products ranged from 3.5~9 and 0.1~2, respectively. The mathematical relationships between the dielectric properties and moisture contents of granular agricultural products were obtained by fitting the experimental data to the microwave frequency (2.45 GHz). This work provides a reference method for measurement of dielectric properties of granular agricultural products, and the theoretical basis for the microwave assisted processing of agricultural products.